2019
DOI: 10.1016/j.bmcl.2019.02.025
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the promiscuity of the chloramphenicol nitroreductase from Haemophilus influenzae towards the reduction of 4-nitrobenzene derivatives

Abstract: Chloramphenicol nitroreductase (CNR), a drug-modifying enzyme from Haemophilus influenzae, has been shown to be responsible for the conversion of the nitro group into an amine in the antibiotic chloramphenicol (CAM). Since CAM structurally bears a 4-nitrobenzene moiety, we explored the substrate promiscuity of CNR by investigating its nitroreduction of 4-nitrobenzyl derivatives. We tested twenty compounds containing a nitrobenzene core, two nitropyridines, one compound with a vinylogous nitro group, and two al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Previous work has demonstrated that the NfsB enzyme from H. influenzae strain Rd KW20 (Hi KW20) has the ability to reduce chloramphenicol to amino-chloramphenicol in vitro ( 15 17 ). Smith et al initially identified several Haemophilus strains, including Hi KW20, and taxonomically unrelated bacterial strains as having the ability to reduce chloramphenicol in bacterial culture ( 12 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work has demonstrated that the NfsB enzyme from H. influenzae strain Rd KW20 (Hi KW20) has the ability to reduce chloramphenicol to amino-chloramphenicol in vitro ( 15 17 ). Smith et al initially identified several Haemophilus strains, including Hi KW20, and taxonomically unrelated bacterial strains as having the ability to reduce chloramphenicol in bacterial culture ( 12 ).…”
Section: Resultsmentioning
confidence: 99%
“…This satisfies the definitions of cryptic and proto-resistance genes and shows potential for clinical relevance through mobilization/change in context and change in expression ( 23 ). Here, we built upon this initial observation ( 15 17 ) to survey the functional landscape of potential chloramphenicol reductases across a range of amino acid identities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, our results provide new insight into the mesotrione transformation by Bacillus megaterium Mes11 strain and highlighted the key physiological role of the NfrA2 enzyme in this process. Nitroreductases being involved in reduction of various nitro-aromatic compounds such as pesticides and antibiotics (Caballero et al, 2005;Symons and Bruce, 2006;Roldán et al, 2008;Carles et al, 2016;El-Hossary et al, 2017;Green et al, 2019), these enzymes (or their genes) could be used as biomarkers to predict the capacity of ecosystems to transform such molecules.…”
Section: Discussionmentioning
confidence: 99%
“…It was first reported in the 1980s that certain bacterial species might be able to evade the toxicity of chloramphenicol through nitro-reduction (Yunis, 1988). More recently it has been proven that a nitroreductase from Haemophilus influenzae is capable of conferring Niclosamide Chloramphenicol chloramphenicol resistance through reduction of the nitro-group (Smith et al, 2007;Crofts et al, 2019;Green, 2019).…”
Section: Niclosamide and Chloramphenicolmentioning
confidence: 99%